Expected Waiting Time for Nonsymmetric Cyclic Queueing Systems—Exact Results and Applications - Sarkar, D.; Zangwill, W. I. (Management Science, 1989)
This paper provides the expected waiting time of a nonsymmetric cyclic server queueing system with Poisson traffic, arbitrary switchover and arbitrary service times. For n the number of queues, the expected waiting time is obtained using n equations which is a significant improvement over the previous best result which requires solution of n 2 equations. Computer, manufacturing and other applications are discussed.